Sleep-dependent clearance of brain lipids by peripheral blood cells - Bumsik Cho; Diane E. Youngstrom; Samantha Killiany; Camilo Guevara; Caitlin E. Randolph; Connor H. Beveridge; Pooja Saklani; Gaurav Chopra; Amita Sehgal (Nature, 2026)
Abstract Sleep is viewed typically through a brain-centric lens, with little known about the role of the periphery 1,2 . Here we identify a sleep function for peripheral macrophage-like cells (haemocytes) in the Drosophila circulation, showing that haemocytes track to the brain during sleep and take up lipids accumulated in cortex glia due to wake-associated oxidative damage. Through a screen of phagocytic receptors expressed in haemocytes, we discovered that knockdown of eater —a member of the Nimrod receptor family—reduces sleep. Loss of eater also disrupts haemocyte localization to the brain and lipid uptake, which results in increased brain levels of acetyl-CoA and acetylated proteins, including mitochondrial proteins PGC1α and DRP1. Dysregulation of mitochondria, reflected in high oxidation and reduced NAD + , is accompanied by impaired memory and lifespan. Thus, peripheral blood cells, which we suggest are precursors of mammalian microglia, perform a daily function of sleep to maintain brain function and fitness.